2013
DOI: 10.1002/ca.22277
|View full text |Cite
|
Sign up to set email alerts
|

The subparietal and parietooccipital sulci: An anatomical study

Abstract: The subparietal and parietooccipital sulci are both located on the medial surface of the brain. Both of these sulci reveal significant variability in pattern and complexity. Both subparietal and parietooccipital sulci play an important role as surgical landmarks using posterior interhemispheric parietooccipital approach to lesions located adjacent to the ventricular trigon deep to the cingulate gyrus. The aim of this study is to analyze variations in the patterns of the subparietal and parietooccipital sulci a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
(17 reference statements)
2
17
2
Order By: Relevance
“…The most common SPS pattern was the H-pattern (45.2 %) followed by the triple upward pattern (23.8 %) in this study. When we compare our results with previous postmortem studies, our results were partially consistent with the results of Gürer et al They also found the H-pattern to be the most common (50 %), followed by the triple upward pattern (19.6 %) [12]. However, the frequency of the other SPS patterns was different in our study than in the Gürer et al study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The most common SPS pattern was the H-pattern (45.2 %) followed by the triple upward pattern (23.8 %) in this study. When we compare our results with previous postmortem studies, our results were partially consistent with the results of Gürer et al They also found the H-pattern to be the most common (50 %), followed by the triple upward pattern (19.6 %) [12]. However, the frequency of the other SPS patterns was different in our study than in the Gürer et al study.…”
Section: Discussionsupporting
confidence: 87%
“…SPS can be connected to only the cingulate sulcus or POS, to neither, or to both [12,23]. The most common connectivity pattern was no connection in our study (41.8 %).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The anatomy of the medial parietal lobe and the safety and complexity of this approach have been previously shown by anatomical reports (11,22). Gurer et al (11) demonstrated the complexities in the patterns of the subparietal and parietooccipital sulci and they showed that these sulci fall within an expected range of variations. Good anatomical knowledge of the medial surface of the parietal lobe is required for surgical approaches through this region.…”
Section: █ Resultsmentioning
confidence: 88%